The c Non-State Actors' Role in the Liberian Civil War - Afolabi, Babatunde Tolu ca. 20./21. Jh (Western Africa Series, 2017)
A detailed examination of the role of two critical non-state groups in the Liberian Civil War peace process - the diaspora and the religious - that provides key insights for policymakers and NGOs into the roles that civil society actors can play in conflict resolution and peacemaking